The Relationship between Sleep Quality, Self- Efficacy, and Stages of Change among the Elderly: A Pilot Study - Mahin Nazari; mostafa taheri; Sareh Keshavarzi; Ali Javadpour (Shiraz University of Medical Sciences, 2014)
Background: Although sleeping problems are common among all age groups, the elderly suffer a higher prevalence of sleep disorders. The present study aimed to investigate the relationship between sleep quality, self-efficacy, and stages of change among the elderly. Methods: This descriptive-analytical study was conducted on 36 individuals aged 60-75 years selected through simple random sampling in 2013. The data were collected using Pittsburgh Sleep Quality Index (PSQI) and self-made structured questionnaires, including sleep self efficacy scale and stages of sleep behavior change scale. SPSS statistical software, version 19 was used to analyze the data and descriptive and inferential statistics such as independent samples t-test were used. Results: The results of the present study revealed that the mean of sleep quality was 7.91 (SD=4.99). In addition, most of the subjects (69%) had poor sleep quality. Considering the stages of change, the participants were in different stages of sleep behavior change. Moreover, a significant relationship was found between self-efficacy and PSQI total score (P<0.001). Also, significant relationships were observed between self-efficacy and the variables of stages of change (P<0.05), except for the average night sleep. Conclusion: The results of this study showed that most of the elderly had poor sleep quality. Besides, they were in different stages of change in sleep problems. The results also indicated that self-efficacy affected the sleep quality in the elderly. Therefore, measures should be taken based on stages of change and increased self-efficacy to improve sleep quality among the elderly.